Sperm associated antigen 4 promotes SREBP1-mediated de novo lipogenesis via interaction with lamin A/C and contributes to tumor progression in hepatocellular carcinoma. (28th June 2022) - Liu, Tengfei; Yu, Junming; Ge, Chao; Zhao, Fangyu; Chen, Jing; Miao, Chunxiao; Jin, Wenjiao; Zhou, Qingqing; Geng, Qin; Lin, Hechun; Tian, Hua; Chen, Taoyang; et al.
Abstract: Hepatocellular carcinoma (HCC) is a highly malignant tumor and its progression is associated with altered lipid metabolism in precancerous lesions, such as non-alcoholic fatty liver disease. Here, we identified sperm associated antigen 4 (SPAG4), and explored its oncogenic role in HCC progression. Database analysis and immunohistochemistry indicated increased level of SPAG4 in HCC tissues which was of prognostic value. Gain/loss-of-function experiments showed that SPAG4 exerted oncogenic roles in HCC growth both in vitro and in vivo . RNA sequencing revealed activation of a lipogenic state and SREBP1-mediated pathway following SPAG4 overexpression. Mechanistically, the N-terminal region of SPAG4 bound to lamin A/C, which increased SREBP1 expression, nuclear translocation, and transcriptional activity. Treatment with orlistat, a lipid synthesis inhibitor, reversed SPAG4-mediated oncogenic effects, and its efficacy varied with SPAG4 level. The effect of orlistat was further amplified when combined with sorafenib in tumor xenograft mouse models. Our study provides evidence that SPAG4 mediates HCC progression by affecting lipid metabolism. Administration of orlistat combined with sorafenib reverses SPAG4-mediated oncogenesis in HCC cells and ectopic xenograft tumors in mice, suggesting that this pathway represents a potential target for HCC treatment. Highlights: High expression of SPAG4 in HCC indicates worse prognosis. SPAG4 facilitates SREBP1-mediated lipogenesis to promote HCC progression. SPAG4 interacts with lamin A/C, affecting SREBP1-mediated lipogenic pathway. Inhibition of SPAG4-mediated lipogenesis with sorafenib restrains tumor growth.